P3-S7.01 Evaluation of a simple point-of-care rapid test for detecting Trichomonas vaginalis among women in Mysore, India. (10th July 2011) - Rao, K; Madhivanan, P; Klausner, J; Trammell, S; Kotian, S; Ravi, K; Krupp, K; Srinivas, V
Abstract : Background: Trichomonas vaginalis is one of the easily treatable sexually transmitted infections in the world. Current methods used to diagnose trichomoniasis rely heavily on training and experience of the technician and have low performance reliability. These methods are unsuitable for settings where accessibility to a continuous electrical source may be a challenge. We examined the performance of OSOM Trichomonas rapid point-of-care test (POC) as compared to the gold standard (culture) and the routine method of diagnosis in clinical laboratories (wet-mount microscopy) in Mysore, India. Methods: Sexually active women over age 18 and seeking care at Prerana Reproductive Health Clinic were enrolled into the study from July 2009 to August 2010. Clinician- collected vaginal swabs were evaluated for trichomonads using wet-mount microscopy, InPouchTM culture, and OSOM® Trichomonas Rapid Test in a blinded manner by different investigators. Results: Of the 417 women enrolled, the prevalence of Trichomoniasis diagnosed by culture was 16.3% (95% CI 12.9% to 20.3%). As compared to culture, the sensitivity, specificity, positive predictive value and negative predictive value for wet mount microscopy was 82.4%, 98.9%, 93.3%, 96.6%; for OSOM rapid test it was 88.2%, 99.4%, 96.8%, 97.8% respectively. Conclusion: OSOM Trich rapid test had very good performance with excellent sensitivity, specificity, positive predictive value, and negative predictive value of 88.2%, 99.4%, 96.8%, and 97.8%, respectively. The implementation of OSOM Trichomonas rapid test would significantly reduce the labour and material costs. Furthermore, frequent partner reinfection as a result of wrong or missed diagnosis can be reduced. It will also reduce other complications such as pelvic inflammatory disease and susceptibility to HIV.